Blockchain technology and its application - Dikariev, Hlib; Miłosz, Marek (Journal of Computer Sciences Institute, 2018)
The article presents the results of analysis of the distributed registry technology called blockchain. The analysis was performed for the possibility of using the blockchain technology in different spheres of human activity.